2022
DOI: 10.1136/bmjopen-2021-058092
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for early childhood growth faltering in rural Cambodia: a cross-sectional study

Abstract: ObjectiveThis study aimed to determine risk factors of growth faltering by assessing childhood nutrition and household water, sanitation, and hygiene (WASH) variables and their association with nutritional status of children under 24 months in rural Cambodia.DesignWe conducted surveys in 491 villages (clusters) randomised across 55 rural communes in Cambodia in September 2016 to measure associations between child, household and community-level risk factors for stunting and length-for-age z-score (LAZ). We meas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 50 publications
1
6
0
2
Order By: Relevance
“…Gains in sanitation coverage attributable to the sanitation intervention were statistically significant but modest when comparing sanitation coverage at the time of our study with pre-intervention estimates in the same communes from 2016 78 (Supporting Information). Community-level OD estimates in the sanitation-only arm decreased by 25 percentage points (pp; 95% CI 23 pp, 27 pp) while OD in the control arm decreased by 19 percentage points (95% CI 17 pp, 20 pp), highlighting the measurable gains attributable to the intervention despite the strong secular trend of sanitation coverage.…”
Section: Discussionmentioning
confidence: 86%
“…Gains in sanitation coverage attributable to the sanitation intervention were statistically significant but modest when comparing sanitation coverage at the time of our study with pre-intervention estimates in the same communes from 2016 78 (Supporting Information). Community-level OD estimates in the sanitation-only arm decreased by 25 percentage points (pp; 95% CI 23 pp, 27 pp) while OD in the control arm decreased by 19 percentage points (95% CI 17 pp, 20 pp), highlighting the measurable gains attributable to the intervention despite the strong secular trend of sanitation coverage.…”
Section: Discussionmentioning
confidence: 86%
“…The distance from a source of water suitable for consumption can be a risk factor; 21 on the other hand, the proper hygienic habit of washing hands, adequate elimination of feces and access to a source of potable water are protective factors for satisfactory growth. 44 , 59 …”
Section: Methodsmentioning
confidence: 99%
“…19,21 In addition, previous studies showed that Poisson regression with robust variance produces correct estimates for the analysis of cross-sectional studies with binary outcomes because the prevalence ratio is more interpretable and simpler to communicate the result. 21,22 The variables with a P -value < .05 were considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%